2013
DOI: 10.3389/fpsyg.2013.00856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive and linguistic ability on gaze behavior in children with hearing impairment

Abstract: In order to explore verbal–nonverbal integration, we investigated the influence of cognitive and linguistic ability on gaze behavior during spoken language conversation between children with mild-to-moderate hearing impairment (HI) and normal-hearing (NH) peers. Ten HI–NH and 10 NH-NH dyads performed a referential communication task requiring description of faces. During task performance, eye movements and speech were tracked. Cox proportional hazards regression was used to model associations between performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…A growing body of research points to co-occurrence of language impairment and other conditions. In our own research comparing children with mild to moderate sensorineural hearing impairment and children with language impairment (e.g., Sahlén and Hansson 2006 , Sandgren et al 2013 ) the findings are consistent with those of other authors (e.g., Briscoe et al 2001 , Gilbertson and Kamhi 1995 ). A considerable proportion of children with hearing impairment have similar problems as children with language impairment, but their problems are generally not as pervasive and persistent.…”
Section: Main Textsupporting
confidence: 90%
“…A growing body of research points to co-occurrence of language impairment and other conditions. In our own research comparing children with mild to moderate sensorineural hearing impairment and children with language impairment (e.g., Sahlén and Hansson 2006 , Sandgren et al 2013 ) the findings are consistent with those of other authors (e.g., Briscoe et al 2001 , Gilbertson and Kamhi 1995 ). A considerable proportion of children with hearing impairment have similar problems as children with language impairment, but their problems are generally not as pervasive and persistent.…”
Section: Main Textsupporting
confidence: 90%
“…The group difference in gaze behavior remained significant despite adjustment for receptive grammar, expressive vocabulary, and complex WMC, but not non-word repetition, revealing an interaction between SNHI and PSTM capacity. Participants with SNHI with lower scores on non-word repetition (>1.25 SD below NH mean) showed a twofold increase in the probability of gaze to the speaker’s face, whereas those with higher scores had a reduced probability of looking at the conversational partner ( Sandgren et al, 2013 ).…”
Section: Language and Communication In Children With Snhimentioning
confidence: 97%
“…In an effort to obtain a fuller picture of the communicative exchanges during referential communication—both speech and body communication—we recently fitted interlocutors with mobile eye trackers ( Sandgren et al, 2012 , 2013 , 2014 ). We were able to show that moments of mutual gaze, in which the listener looks at the speaker, showed a tight temporal connection with important parts of the spoken message ( Sandgren et al, 2012 ).…”
Section: Language and Communication In Children With Snhimentioning
confidence: 99%
See 1 more Smart Citation
“…Ricketts and Galster (2008) reported that children with hearing loss were more likely to turn toward brief utterances by secondary talkers in classrooms than were children with NH, and suggested that such attempts could have negative consequences if they draw attention away from the primary talker. Sandgren and colleagues (Sandgren et al 2013; 2014) reported that children with bilateral mild-moderate hearing loss were more likely to look at the face of their partner with NH during a dyadic referential communication task than vice versa. The same may be true for children with MBHL or UHL, for whom the auditory signal is degraded in a more chronic and persistent way than in peers with NH.…”
Section: Introductionmentioning
confidence: 99%